Pendidikan Anti Diskriminasi Sejak Dini: Implementasi Nilai HAM pada Anak Usia Dini - Ratna Nuri Nahya; Adinda Tahnia; Zaenul Slam (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
Early anti-discrimination education is a strategic step in developing children's character that respects differences and upholds human values. This article aims to examine the implementation of human rights values in early childhood education as an effort to prevent discriminatory attitudes in the future. The method used is a reference list analyzing various sources related to civics, human rights, and early childhood development. The results show that instilling human rights values can be done through simple and contextual learning activities, such as playing together, sharing, respecting friends, and introducing diversity in a positive way. The role of educators and the environment is crucial in providing role models and creating an inclusive atmosphere for children. Therefore, the implementation of human rights values from an early age is expected to shape a generation that is tolerant, just, and respectful of the rights of others in society, the nation, and the state.